Genome-wide characterization of cys-tathionine-β-synthase domain-containing proteins in sugarcane reveals their role in defense responses under multiple stressors - Zhou, Jing-Ru; Li, Juan; Lin, Jia-Xin; Xu, Hui-Mei; Chu, Na; Wang, Qin-Nan; Gao, San-Ji (Frontiers in Plant Science, 2022)
Cys-tathionine-β-synthase (CBS) domain-containing proteins (CDCPs) are essential for regulating plant responses to various biotic and abiotic stressors. This study describes the systematic identification and characterization of CDCP family genes in Saccharum spontaneum. A total of 95 SsCDCP genes and eight phylogenetic groups were identified that were distributed over 29 chromosomes of the AP85-441 genome. Most (78/95) SsCDCPs underwent fragment duplication events, and 64 gene pairs were located in synteny blocks. Expression profiling of nine ShCDCPs was also carried out in the Saccharum spp. cultivars ROC22 and MT11-611 that are resistant and susceptible to red stripe, respectively, in response to: (i) Infection by the bacterial pathogen Acidovorax avenue subsp. avenae (Aaa); (ii) abiotic stressors (drought and salinity); and (iii) exogenous salicylic acid (SA) treatment. Members of one gene pair (ShCBSD-PB1-5A and ShCBSD-PB1-7A-1) with a fragment duplication event acted as negative regulators in sugarcane under four stresses, as supported by the significantly decreased expression levels of ShCBSD-PB1-5A (23–83%) and ShCBSD-PB1-7A-1 (15–75%) at all-time points, suggesting that they have functional redundancy. Genes in another pair, ShCBS-4C and ShCBS-4D-1, which have a fragment duplication event, play opposing regulatory roles in sugarcane exposed to multiple stresses, particularly Aaa and NaCl treatments. ShCBS-4C expression was significantly decreased by 32–77%, but ShCBS-4D-1 expression was dramatically upregulated by 1.2–6.2-fold in response to Aaa treatment of both cultivars across all-time points. This result suggested that both genes exhibited functional divergence. Meanwhile, the expression of SsCBSDCBS-5A was significantly upregulated in ROC22 by 1.4–4.6-fold in response to the four stressors. These findings provide important clues for further elucidating the function of ShCDCP genes in sugarcane responding to a diverse range of stresses.